PENGEMBANGAN MEDIA YOUTUBE SHORT VIDEO PENCEGAHAN DIABETES MELITUS - Abdullah, Muhammad Hizbi Abdullah; Lestari, Febri Sri (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Indonesia ranks 5th globally in diabetes mellitus cases, with prevalence rising annually among individuals over 18. Health promotion media are essential for educating people, especially those aged 18-64, on diabetes prevention. YouTube Shorts is an effective medium due to its accessibility, enhancing attention to health information. Purpose: To produce YouTube Shorts as health promotion media regarding diabetes mellitus prevention for the audience and subscribers of the Smart Generations of Reality YouTube channel. Method: The research type utilizes Research and Development (R&D) with a 4D development model (define, design, development, disseminate). Result: The define stage revealed that the Smart Generations of Reality channel audience lacks awareness of diabetes prevention. The target audience prefers anime-style YouTube Shorts, which match their characteristics. The